Trial of Cholinergic Agonist in Adults with ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A novel cholinergic activating agent, ABT-418, was used to treat 29 adults with ADHD, in a double-blind, placebo-controlled, randomized, crossover trial at the Pediatric Psychopharmacology Clinic, Massachusetts General Hospital, Boston.